Ways We Allegorize Now: Transforming Texts and Bodies from the Roman de Renart to Daniel Paul Schreber's Memoirs and Chris Morris's Four Lions. (June 2014) - S, J R.
Abstract : How stable are understandings of "surface, " and how might we best contextualize or historicize appeals to it as a limit that defines experiences and constructions of the body and the world? Disorientations with regard to surface and depth have informed discourses on allegorical interpretation, psychotic delusion, and religious fundamentalism, not to mention practices of rewriting and reworking. Accordingly, this study draws together comparative readings of late episodes of the Roman de Renart, Daniel Paul Schreber's Memoirs of My Nervous Illness, and Chris Morris's Four Lions, a satirical reflection on British jihadism. All three works foreground radical disturbances of relations between inside and outside, surface and depth. The diverse cultural pressures evident here find shared ground in their subversive mapping of anxieties regarding spirit and body, sublimation and pollution. In both the Renart and Schreber's Memoirs, these transformations also reflect the energies underpinning textual and reading practices whose complexities are evident in the baffling but productive convolutions of authorial reworking. Alongside any "we" that may feel driven to render surface its historical and ethical due, there are invariably other readers and, crucially, writers who are compelled by their own equally pressing reasons not to let surface be.